Kontribusi Komunikasi Antarbudaya dalam Pemahaman Keberagaman pada Program Pertukaran Pemuda Antar Provinsi 2024 - Dzaky Furqon Kurnia; Nani Nurani Muksin (Lembaga Pengembangan Kinerja Dosen, 2026)
The pivotal role of youth in the continuity of the Indonesian nation is crucial as a means of renewing ideas, which subsequently serves as tangible evidence for change. The Government also plays a vital role in facilitating youth advancement. The Inter-Provincial Youth Exchange Program (PPAP), implemented by the Ministry of Youth and Sports, is a flagship initiative designed to educate youth across all aspects as a form of societal training. The objective of this program is to support the improvement of the Youth Development Index (YDI) and to realize the nation's aspirations for the Golden Generation of 2045. While every young person faces unique challenges and ideological differences, a common goal can be established by unifying perceptions into a single voice: a developed Indonesia. Through this program, it is expected that the youth delegates and participants will gain constructive perspectives to achieve their aspirations. These differences and youth viewpoints are articulated in this report to serve as a reference for viewing the world more broadly. This research was conducted using case studies and direct observational interviews, with the results compiled into this final project report as a thesis achievement.